2020
DOI: 10.26452/ijrps.v11i1.1913
|View full text |Cite
|
Sign up to set email alerts
|

Study of the effect of different levels of arginine in feed on broiler chickens

Abstract: Amino acids are the basic structural units of protein molecules in the body. Currently, about 300 amino acids are known, of which 26 are studied best. Amino acids or their derivatives (for example, immune bodies) are part of enzymes, hormones, pigments, and other specific substances that play a crucial role in digestive and metabolic processes. In the process of metabolism, many amino acids are synthesized in the body from other amino acids or compounds, and therefore they are called interchangeable. Amino aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 5 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…The results of our studies showed that biofilm formation involves adhesion, fixation, microcolony formation, growth, and dispersion stages. The main stages of the in vitro development of biofilms of Gram-negative and Gram-positive bacteria and yeastlike fungi have been sufficiently studied and covered in detail in the literature [8,[33][34][35]. Effective methods for recording the bacterial mass and volume of the intercellular matrix of monospecies and polyspecies biofilms [32,36] have been developed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of our studies showed that biofilm formation involves adhesion, fixation, microcolony formation, growth, and dispersion stages. The main stages of the in vitro development of biofilms of Gram-negative and Gram-positive bacteria and yeastlike fungi have been sufficiently studied and covered in detail in the literature [8,[33][34][35]. Effective methods for recording the bacterial mass and volume of the intercellular matrix of monospecies and polyspecies biofilms [32,36] have been developed.…”
Section: Discussionmentioning
confidence: 99%
“…After 1-2 h of interaction between S. aureus ATCC 29213 and human cell culture HT-29, most bacteria were located in the intercellular space. Colonization of the eukaryotic cell surface by bacterial cells was visualized after 3 h. Complete disorganization of the cell layer and destruction of eukaryotic cells was observed after 24 h [33]. Due to the growing resistance of S. aureus to various antibiotics, great efforts have been made to identify new antibacterial compounds.…”
Section: Discussionmentioning
confidence: 99%